Public Enemy No. 1?: Understanding Media Representations of Outlier Views on Climate Change. (June 2013) - Boykoff, Maxwell T.
Outlier voices—particularly those views often dubbed climate "skeptics, " "denialists, " or "contrarians"—have gained prominence and traction in mass media over time through a mix of internal workings such as journalistic norms, institutional values and practices, and external political economic, cultural, and social factors. In this context, the article explores how and why these actors—through varied interventions and actions—garner disproportionate visibility in the public arena via mass media. It also examines how media content producers grapple with ways to represent claims makers, as well as their claims, so that they clarify rather than confuse these critical issues. To the extent that mass media misrepresent and/or gratuitously cover these outlier views, they contribute to ongoing illusory, misleading, and counterproductive debates within the public and policy communities, and poorly serve the collective public. Furthermore, working through mass media outlets, these outlier interventions demonstrate themselves to be (at times deliberately) detrimental to efforts seeking to enlarge rather than constrict the spectrum of possibility for varied forms of climate action.